Evaluation of the optical properties of various-shaped and core-shell-structured lanthanum hexaboride nanoparticles based on discrete dipole approximation. (September 2021) - Chao, Luomeng; Sun, Changwei; Shu, Qunwei; Liu, Jia; Xiao, Lihua
Highlights: Extinction efficiencies of various shaped and core-shell structured LaB6 nanoparticles has been studied by discrete dipole approximation. Rod-like structure has more advantages in extinction at long wavelength. LaB6 @TiO2, LaB6 @ZnO and LaB6 @SiO2 exhibits preferable transparent heat shielding performance, which is expected to solve the long-term stability of LaB6 in the actual environment. Abstract: The extinction behavior of various-shaped and core-shell-structured lanthanum hexaboride (LaB6 ) nanoparticles was theoretically studied based on the discrete dipole approximation method. It was found that different nanoparticle shapes yielded a great influence on extinction efficiency. In comparison to spherical and cubic particles, the near-infrared (NIR) extinction peak of rod-like nanoparticles appeared at a longer wavelength. For core-shell-structured LaB6 particles, all of LaB6 @TiO2, LaB6 @ZnO, and LaB6 @SiO2 exhibited low extinction in the visible region and high extinction in the NIR region, indicating that these three structures are potential transparent heat-shielding materials. Moreover, LaB6 @TiO2 manifested better NIR extinction behavior than LaB6 @ZnO and LaB6 @SiO2 ; however, its transmittance in the visible region was slightly reduced.